The relational economy: geographies of the knowing and learning - Bathelt, Harald; Glückler, Johannes (Oxford University Press, 2011)
How are firms, networks of firms and production systems organised and how does this organisation vary from place to place? This book synthesises theories from across the social sciences with empirical research and case studies in order to answer this question.
Keywords: Anthropogeografie